Synthesis and Characterization of Copper(II) Oxide (CuO-NP) Nanoparticles using Chemical Precipitation Method - Charlena Charlena; Sri Sugiarti; Dila Ardiansyah (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
This study aims to optimize the calcination temperature and see the effect of adding surfactant on the bandgap, particle size, crystallinity level of CuO nanoparticles (CuO-NP), and the activity of CuO nanoparticles as an antibacterial agent. CuO-NP was successfully synthesized using the chemical precipitation method with variations in calcination temperature of 400, 600, and 800 °C with NaOH as a precipitating agent. The synthesized nanoparticles were further characterized using a UV-Vis, XRD, and SEM-EDX spectrophotometer. The value of the CuO-NP bandgap increases with increasing temperature. The bandgap gets bigger when the absorbance value gets smaller. Increasing the calcination temperature causes the crystal size of CuO-NP to become larger. The best level of crystallinity of CuO-NP was obtained at 68,31% with a calcination temperature of 600 °C. Adding 1% PVP did not significantly prevent agglomeration between CuO-NP particles, thereby increasing the size of CuO-NP particles. Keywords: bandgap, CuO-NP, PVP, temperature